Acceptance and use of E-Government services among employees in government high education institution in Jalan Hang Tuah / Muhammad Irsyanuddin Kerma - Kerma, Muhammad Irsyanuddin (Faculty of Business and Management, 2018)
E-Government have been used since 90’s worldwide as a platform in connecting the government and its citizens. Even though, many people still do not recognize its usage and benefits that they can gain from it. This study thus aims to investigate the relationship between four acceptance factors towards the acceptance and use of E-Government services among employees in government high education institution in Jalan Hang Tuah.